Numerical investigation of thermal discharge to coastal areas: A case study in South Italy. (February 2020) - Gaeta, Maria Gabriella; Samaras, Achilleas G.; Archetti, Renata
Abstract: Coupled wave – 3D-hydrodynamics model runs are performed to investigate thermal discharge release to coastal areas by means of including nearshore effects of wave-current dynamics. The study area comprises the vicinity of a power plant at Cerano, in South Italy, where cooling industrial waters are released to the sea. The implemented model is calibrated by using temperature measurements and sensitivity analyses are carried out for various relevant drivers and input parameters. Afterwards, the effect of thermal discharge is investigated through distinct hypothetical scenarios for a combination of metocean conditions and operational features of the power plant (modifying water discharge and temperature at its outlet). The model results of this representative array of conditions are intercompared and evaluated on the basis of heat dispersion rate and areas of influence, providing with useful insights on the numerical simulation of the process and the potential effects for the specific coastal area. Highlights: Thermal release dynamics in sea was studied by a wave – 3D-hydrodynamics model. Sea temperature measurements were used to calibrate the model. Sensitivity analyses highlighted the importance of including wave – wind modelling. Turbulence, vertical diffusion and wind drag coefficients were found key-parameters. Environmental and operational scenarios revealed changes in thermal plume.